A rare case of Contusio Cordis: Fist fight leading to an Acute Myocardial Infarction due to Left Anterior Descending artery dissection - Hiten Patel; Yamini Sundermurthy; Suchit Bhutani; Mahesh Bikkina (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2017)
Cardiac lesions resulting from blunt chest injuries can present as cardiac contusion; ventricular free wall rupture; ventricular septal rupture; and valvular lesion [1]. But acute Myocardial infarction (MI) from contusio cordis is a very rare complication. Here we present a case of fist punch to the chest leading to distal Left Anterior Descending (LAD) artery dissection causing acute MI.